2015
DOI: 10.1111/apt.13307
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic analysis of factors associated with progression and regression of ulcerative colitis in 918 patients

Abstract: SUMMARY BackgroundStudies that systematically assess change in ulcerative colitis (UC) extent over time in adult patients are scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Safroneeva and colleagues did not find an association between BMI and risk of disease extension 9 . However, in their study, rate of disease extension was compared between individuals with BMI greater than 20 to those less than 20.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Safroneeva and colleagues did not find an association between BMI and risk of disease extension 9 . However, in their study, rate of disease extension was compared between individuals with BMI greater than 20 to those less than 20.…”
Section: Discussionmentioning
confidence: 93%
“…In most patients with initial diagnosis of proctitis, the disease does not extend to more proximal areas of the large intestine. Specifically, prior studies suggest that only 10–30% of patients with ulcerative proctitis experience disease extension 49 .…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing question is what proportion of cases do not extend proximally but remain as UP over time. In an analysis from the Swiss IBD cohort study it was found that one-third of patients increased their initial disease extent over a median follow-up period of 9 years [10]. Likewise, an Italian study found that 27% of UP cases had proximal extension over a mean follow-up period of just 5 to 6 years [11].…”
Section: Course Over Timementioning
confidence: 99%
“…In the EpiCom 2010 incidence cohort 20% of UC cases in Western Europe and 22% in Eastern Europe were defined as UP at presentation (5-year follow-up data are due to be published in the next year) [9]. The most recent report was a Swiss study, which found a ratio of 4.2:3.7:2.2 for extensive UC, distal UC and UP at time of diagnosis [10]. In summary, 22% -33% of UC cases present as UP at time of disease diagnosis.…”
Section: Incidencementioning
confidence: 99%
“…A prospective study of Norwegian UC patients found that at the time of presentation, colitis was limited to the rectum (proctitis) in one third of patients, the colorectum distal to the splenic flexure (left-sided colitis) in another third, and the area proximal to the splenic flexure (extensive colitis) in the remaining third ( 2 ). In patients with distal colitis, inflammation progresses in 25–50% of patients, while regression is observed in about 16% of patients ( 3 , 4 ). The anatomical extent of mucosal inflammation is one of the most important factors determining disease course.…”
Section: Introductionmentioning
confidence: 99%